THE ESSENCE OF TAX OPTIMIZATION (Research Bulletins of the Faculty of Economic Sciences, 2025)
Tax optimization constitutes a crucial element of financial management for enterprises, enabling the minimization of tax burdens within the boundaries of the law. This article discusses the definition, assumptions, and significance of tax optimization in the context of corporate financial strategy. It outlines the objectives of optimization as well as the risks associated with it. The article includes the results of survey research on entrepreneurs' awareness of tax optimization, highlighting a tendency to choose specific forms of business activity to reduce tax liability. It also explores how Polish entrepreneurs perceive and apply tax optimization, identifying the most commonly used methods and strategies in this area. The article emphasizes the necessity of understanding and appropriately applying current regulations to ensure that business activities remain lawful and support long-term growth.
Keywords: tax optimization, business activities, strategies